Antiulcerogenic effect of Cuphea ignea extract against ethanol-induced gastric ulcer in rats - Amria M. Mousa; Nermin M. El-Sammad; Sherien K. Hassan; Abd El Nasser A. Madboli; Amani N. Hashim; Eman S. Moustafa; Sherien M. Bakry; Elsayed A. Elsayed (BMC, 2019)
Abstract Background Cuphea ignea is one of the herbal resources belonging to Lythraceae family. Some species of this family have been used traditionally in South and Central America's folk medicine for treating stomach disorders. Therefore, the present study was performed to evaluate the gastropreventive effect of aqueous ethanolic extract of C. ignea aerial parts on ethanol-induced gastric ulcer. Methods Gastric ulcers were induced in Sprague Dawley rats using one oral dose of absolute ethanol (1.5 mL/rat). The C. ignea aerial parts extract at doses of 250 and 500 mg/kg body weight and ranitidine (a reference drug) at a dose of 30 mg/kg body weight were orally administrated daily for 7 days before ulcer induction. One hour after ethanol administration blood samples were collected and then stomachs of sacrificed rats were subjected to biochemical, macroscopic and microscopic studies. Results Oral administration of C. ignea extract significantly attenuated gastric ulcer as revealed by significant reduction in the gastric ulcer index and volume of gastric juice while significantly increased preventive percentage, gastric pH value and pepsin activity. Pre-treatment of C. ignea extract markedly improved the serum level of TNF-α, the gastric MPO activity and NO content. Furthermore, C. ignea pre-treatment significantly increased the gastric levels of enzymatic and non- enzymatic antioxidants namely CAT, SOD, GSH-Px, and GSH with concomitant reduction in MDA level compared with those in the ethanol group. These results were further supported by histopathological findings which revealed the curing effect of C. ignea on the hemorrhagic shock induced by ethanol toxicity. Conclusions C. ignea extract showed a potential gastroprotective effect on ethanol-induced gastric ulcer, and its effect may be mediated through suppression of oxidative stress and gastric inflammation.